(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2026)
This study aimed at finding out students’ improvement of speaking skill and investigating students’ responses after using short video with imitation technique. This study used pre-experimental method with pre-test and post-test was conducted at SMP Negeri 12 Makassar at grade VII students with a population of 32 students in one class, while the sample was the VII-1 consisting of 22 students. The instruments of data obtained by giving a set of speaking tests in the form of oral tests and questionnaires. The data analysis was used SPSS 26. In addition, the result of this study that has been conducted by the students in the pre-test was 19.16, while in the post-test was 13.60. Furthermore, the study found that the t-score value in this study was higher than the significance value (ts = 9.267 > sig.2 tailed = 0.00). So, the results of this study that had been done could be an alternative in improving students’ speaking skill. Then, students also gave positive responses regarding the technique and the media that used by the researcher.